2018
DOI: 10.1016/j.pharep.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitizing effects of metformin on cisplatin- and paclitaxel-resistant ovarian cancer cell lines

Abstract: Taken together, our observations suggest that metformin inhibits the inflammatory pathway induced by paclitaxel and cisplatin treatment. Furthermore, metformin in combination with paclitaxel or cisplatin improved the sensitivity in drug-resistant ovarian cancer cells. Therefore, metformin may be beneficial treatment strategy, particularly in patients with tumors refractory to platinum and taxanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…This major cytotoxicity was due to a synergic effect of Metf and MAL-PDT and not to an additive effect. Our results are in agreement with other studies and indicate that Metf improves the cytotoxicity induced by PDT with 5-aminolevulinc acid in human oral squamous cell carcinoma [41] or by chemotherapy using paclitaxel or cisplatin in other cell lines [42,43].…”
Section: Discussionsupporting
confidence: 93%
“…This major cytotoxicity was due to a synergic effect of Metf and MAL-PDT and not to an additive effect. Our results are in agreement with other studies and indicate that Metf improves the cytotoxicity induced by PDT with 5-aminolevulinc acid in human oral squamous cell carcinoma [41] or by chemotherapy using paclitaxel or cisplatin in other cell lines [42,43].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Li et al (48) demonstrated that metformin can increase the survival rate of diabetic patients with gastric cancer. Previous studies have demonstrated that metformin inhibits cell proliferation and induces cell death in various types of cancer cells, including HepG2 hepatoma cells (49), SKOV3, A2780 and ES2 ovarian cancer cells (50,51), paclitaxel-resistant A2780-PR and cisplatin-resistant ACRP cells (52), B16F10 melanoma cells (53), Dami and MEG-01 megakaryoblastic cancer cells (54), and CAL 27, CAL 33, and UMSCC47 head and neck carcinoma cells (55). Furthermore, metformin also suppresses the cell metastasis of MG63 and U-2 OS osteosarcoma cells (56), SiHa and HeLa cervical cancer cells (57), and EC109 esophageal squamous cells carcinoma cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…45,49,50 Interestingly, recent studies show that metformin, usually applied in diabetic patients, prevents tumor growth, induces apoptosis and increases sensitivity to chemotherapy in ovarian cancer cells. [51][52][53][54][55][56][57] Mechanisms underlying these cellular effects include suppression of cancer stem cells, inhibition of epithelial-to-mesenchymal transition and interference with neoplastic cell metabolism. [58][59][60][61][62] Following promising data of epidemiological studies showing a favorable effect of metformin on ovarian cancer Figure 6 Summary of the hypothesized interaction within the NRF2/AKR1C1/PR pathway.…”
Section: Discussionmentioning
confidence: 99%